Lithium-Sulfur battery technology readiness and applications – a review - Fotouhi, Abbas; Auger, Daniel J.; O’Neill, Laura; Cleaver, Tom; Walus, Sylwia (MDPI, 2017)
Lithium Sulfur (Li-S) battery is generally considered as a promising technology where high energy density is required at different applications. Over the past decade, there has been an ever increasing volume of Li-S academic research spanning materials development, fundamental understanding and modelling, and application-based control algorithm development. In this study, the Li-S battery technology, its advantages and limitations from the fundamental perspective are firstly discussed. In the second part of this study, state-of-the-art Li-S cell modelling and state estimation techniques are reviewed with a focus on practical applications. The existing studies on Li-S cell equivalent-circuit-network modelling and state estimation techniques are then discussed. A number of challenges in control of Li-S battery are also explained such as the flat open-circuit-voltage curve and high sensitivity of Li-S cell’s behavior to temperature variation. In the last part of this study, current and future applications of Li-S battery are mentioned.
Keywords: lithium-sulfur battery; application; technology readiness; review